Reading Literacy Movement in Elementary School / Gerakan Literasi Membaca di Sekolah Dasar - Nida Helwa Hanin; M. Irfan Islamy (Al-Mudarris: Journal Of Education, 2020)
The purpose of this study is identifying the problematics the implementation of the Reading Literacy Movement in Primary Schools. The approach in this research is qualitative with descriptive type. Data collection techniques in this study used observation, interviews, and documentation. This research was conducted at SDN X in Malang City. The results showed that the problem of the Reading Literacy Movement at SDN X in Malang was divided into 3 categories, namely the 15 minute reading habit, with the problem of reading and writing skills and the ability to understand student reading, limited reading time, low motivation and interest in reading. At the facility and facility enrichment stage category, with the problem of the availability various books in the library, limited reading areas, reading angles, and literacy posters. The category of supporting resources, with the problem of reading literacy climate, teachers and literacy reading teams, parental and community support.